Influence of perceived social support on detection of social norm violation: evidence from N1 and N400 - Liang, Bing; Li, Bingbing; Fan, Xiaoyue; Mu, Yan; Wang, Juan (Frontiers in Psychology, 2024)
Introduction The perceived social support individuals receive from their others plays a crucial role in shaping conformity with social norms. However, the specific mechanism underlying perceived social support and the detection of social norms remains unclear. Methods In this study, college students with high and low levels of perceived social support were asked to judge the appropriateness of stranger’s behaviors (e.g., singing) in different situations (e.g., library). The participants’ electroencephalography activities were analyzed aiming to uncover the neural mechanism underlying how perceived social support influences the detection of others’ normative behavior. Results The ERP results indicate that, for individuals with a lower level of perceived social support, larger amplitudes of the N1 component (related to primary processing) and the N400 component (related to cognitive conflict) were observed when detecting others’ social norm violation compared to the conformity condition. However, for individuals with a higher level of perceived social support, no significant differences were found in detecting others’ conformity or violation of social norms. Discussion The results indicate that, when the perceived social support level of the individual is low, detecting others’ social norm violation elicits deeper primary processing and stronger cognitive conflict compared to conformity condition.